2011
DOI: 10.1016/j.jcrysgro.2010.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Germanium doping for improved silicon substrates and devices

Abstract: During the last decade, the 300 mm silicon wafer has been optimized and one is studying the move to 450 mm crystals and wafers. The ever increasing silicon crystal diameter leads to two important trends with respect to substrate characteristics: the interstitial oxygen concentration decreases while the size of grown in voids (COP's) in vacancy-rich crystals is increasing.The first effect is due to the large melt in which movements have to be controlled and partly suppressed by the use of magnetic fields. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
(69 reference statements)
2
10
0
Order By: Relevance
“…These impurities interact with vacancies and interstitials, and can therefore be used to affect interactions of point defects during crystal growth, during device processing as well as under irradiation. Although a huge amount of experimental and theoretical data have been collected during the last decades, our understanding of intrinsic point defect‐impurity reactions is not yet definitive, see, for example 1–9 and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…These impurities interact with vacancies and interstitials, and can therefore be used to affect interactions of point defects during crystal growth, during device processing as well as under irradiation. Although a huge amount of experimental and theoretical data have been collected during the last decades, our understanding of intrinsic point defect‐impurity reactions is not yet definitive, see, for example 1–9 and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nucleation of oxide precipitates at lower temperatures and the slower oxygen diffusion, oxide precipitates can indeed only grow to a maximum size of about 20 nm during a crystal pulling process. The previously reported differences in COP size between silicon wafers with and without Ge doping, 9,15 are most probably due to the fact that only the tail of the COP size-density distribution with the largest defects can be observed with the surface inspection tools. 14 The void data in Table I suggest also that with respect to defect size/density distribution, no significant differences exist between the crystals with and without Ge doping and even not between the 4 and 6 in.…”
mentioning
confidence: 98%
“…It has been widely accepted that O i atom migrates via jumping between neighboring SiSi bond centers, which is strongly influenced by high concentrations of dopant atoms in silicon. It has been reported that the oxygen diffusion can be retarded or enhanced by dopant atoms such as arsenic (As) , antimony (Sb) , boron (B) , carbon (C) , and germanium (Ge) . The mechanism underpinning such influence is usually understood as dopant trapping or vacancy‐mediated dopant trapping .…”
Section: Introductionmentioning
confidence: 99%